Copepod Behavior Responses Around Internal Waves - Mohaghar, Mohammad; Jung, Seongyu; Haas, Kevin A.; Webster, Donald R. (Frontiers in Marine Science, 2020)
Internal waves are ubiquitous features in coastal marine environments and have been observed to mediate vertical distributions of zooplankton. Internal waves possess fine-scale hydrodynamic cues that copepods and other zooplankton are known to sense, such as fluid density gradients and velocity gradients (quantified as shear strain rate). The role of copepod behavior in response to cues associated with internal waves is largely unknown. The objective is to provide insight to the bio-physical interaction and the role of biological versus physical forcing in mediating organism distributions. A laboratory-scale internal wave apparatus is designed to facilitate fine scale observations of copepod behavior in flows that replicate in situ conditions of internal waves in two-layer stratification. An experimental configuration is presented with a density jump of 1 sigma_t. Theoretical analysis of the two-layer system provided guidance to the target forcing frequency needed to generate a standing internal wave with a single dominate frequency of oscillation. Flow visualization and signal processing of the interface location were used to quantify the wave characteristics. The results show a close match to the target wave parameters. Marine copepod (mixed population of Acartia tonsa, Temora longicornis, and Eurytemora affinis) behavior assays were conducted for three different physical arrangements: (1) no density stratification (i.e. control), (2) stagnant two-layer density stratification, and (3) two-layer density stratification with internal wave motion. Digitized trajectories of copepod swimming behavior indicate that in the control (case 1) the animals showed no preferential aggregation. In the stagnant density jump treatment (case 2) copepods preferentially moved horizontally, parallel to the density interface. In the internal wave treatment (case 3) copepods demonstrated loopy, orbital trajectories near the density interface. Analysis of advected trajectories in the internal wave, with and without superimposed copepod swimming, reveal distinct differences with the observed copepod trajectories in the internal wave treatment. These differences and a consideration of the potential hydrodynamic cues indicate that copepod behavior response has a substantial influence on the swimming trajectories in the internal wave region.